GENE POLYMORPHISM FOR Î‘-RECEPTOR OF OESTROGENES AND ALTERATIONS IN BONE MINERAL DENSITY FOR ADULT CELIAC DISEASE PATIENTS - Hassan, Khodor Haidar; Paoli, Beatrice; Prada, Edwin Parra; Semaan, Pierre; Abdallah, Rony; Berri, Fadwa; Khatir, Houria; Nasreddine, Salam; Ezzedine, Mohamad; Mortada, Mohamad (European Scientific Journal, ESJ, 2015)
It is well known that osteopenia and osteoporosis are frequently found celiac disease patients presenting classical symptoms of malabsorption1. Osteomalacia cases have also been diagnosed in celiac patients who do not present clinical signs of malabsorption , in patients with latent celiac disease, as well as in first degree relatives of patients with celiac disease who do not suffer from celiac disease themselves. This suggests the presence of different pathogenic mechanisms2. The analysis of genetic polymorphism represents an effective approach for an in-depth screening of genes potentially implicated in the development of osteoporosis. Because of the central role that estrogen plays in bone metabolism, ER genes play an important role in the determination of bone mineral density and the risk of osteoporosis. The fact that osteoporotic phenotypes are observed in patients with a destructive mutation of the Î± receptor gene for estrogen together with the signs of reduced bone mineral density that are found in mice presenting a functional insufficiency of ER Î±, but not in mice showing reduced ER Î² function, demonstrates that ER Î± is one of the principal genes involved in the genesis of osteoporosis3. Previously , two intronic polymorphisms of the Î± ER gene, identified by restriction endonucleases PvuII and TA Xba and repetitive polymorphism sequences, have been linked to bone mass density in the Japanese population and in menopausal Italian women4.